The role of industry technologies in is education: a South African case study - Mutetwa, Shaloam (Department of Information Systems, 2023)
The issue of determining the most appropriate software tools for instructional purposes is not new. As the tools keep changing and evolving and considering the vast number of existing tools that are there, this process of selecting the best tools for students may become quite challenging and it is important that the dynamic be explored. This research targets studying factors that have impact on tool selection, implementation of tools in the curriculum, and impact of tool use on students. The study also uses Activity Theory as the theoretical framework in holistically exploring how these tools are implemented in an undergraduate Information Systems curriculum. The research adopts an interpretivist approach and follows an exploratory research design using qualitative methods to gather data and thematic analysis for data analysis. This case study is of a South African university, which was chosen using convenience sampling. Data was collected through interviews with 10 lecturers and 8 students at the Information Systems Department and analysis of course outlines. Key findings point to alignment with industry needs, affordability, availability of supplementary resources, and software functionality as some of the important criteria used by educators when selecting software products. The study also identifies primary and secondary contradictions as per the Activity Theory and these highlight the inconsistencies which exist in the department's use of technologies. It is important to note the lack of studies in this area, where existing research mainly focuses on tools used in specific courses in Information Systems, but none have looked at the Information Systems discipline as a whole. The study also highlights the different roles played by technology companies in facilitating the use of tools in courses, which to the researcher's knowledge, has never been done before. Thus, the research contributes to literature and fills the stated gaps in research and answers the research questions.